How to bridge the climate finance gap and support smallholders in food systems transformation - Environmental Defense Fund; International Fertilizer Association; Southern African Confederation of Agricultural Unions; International Rice Research Institute (UN Climate Change, 2022)
Current financing for climate action in food systems is insufficient for the transformation required. This session will focus on the role of climate finance in assisting producers, especially smallholders, and how to engage them in transitioning to low-carbon agriculture while improving livelihoods. Speakers: Lini Wollenberg, Alliance of Bioversity & CIAT, & University of Vermont Ishmael Sunga, Southern African Confederation of Agricultural Unions Alzbeta Klein, International Fertilizer Association Jochen Flasbarth, BMZ. Moderator: Dhanush Dinesh, Clim-Eat Fred Krupp, Environmental Defense Fund